Damage process in glass fiber reinforced polymer specimens using acoustic emission technique with low frequency acquisition. (15th January 2021) - Friedrich, Leandro; Colpo, Angélica; Maggi, Anna; Becker, Tiago; Lacidogna, Giuseppe; Iturrioz, Ignacio
Highlights: The AET is applied in the damage evolution of a GFRP plate during a bending test. AE signals were identified by using a proposed algorithm based in a threshold level. Several global parameters allowed to show different aspects of the damage evolution. Abstract: The damage process in fiber-reinforced polymers (FRP) has been the subject of continuous studies in recent decades using different approaches. In particular, the acoustic emission technique has been proved to be a powerful tool in the monitoring of structures of this type of material due to the large acoustic activity captured when this material is loaded to rupture. The present work explores several indexes that were calculated from the experimental recording of acoustic emission signals, and their efficiency in describing the failure process in structures. One of these indexes, called c value, is originally proposed, and its sensibility it is compared with other classical parameters that are usually employed in the Acoustic Emission analysis. A 3-point bending test has been performed on a glass fiber reinforced polymer plate. Our own methodology was proposed to identify AE signals in semi-automatic manner. This methodology also allowed a faster analysis of the global parameters during the process data of the AE test. The global parameter evolution obtained from the acoustic emission data during the damage process could be considered as precursors of the more meaningful event and as an aid to understand in which way the structure is going to the collapse.